Second Dialect Acquisition by North Korean Refugee Speakers: Acquiring Seoul Korean Stops. - Lee, Jungah; Idemaru, Kaori; Vaughn, Charlotte (Language & Speech, 2026)
This study examined Korean three-way stop contrasts produced by North Korean (NK) immigrant speakers now living in South Korea, from the perspective of second dialect acquisition (SDA). Their production was compared with that of South Korean (SK) speakers. SK speakers and NK refugee speakers (N = 22 each) completed three tasks designed to elicit careful and conversational speech: reading aloud lists of one-syllable words and short phrases and participating in a sociolinguistic interview. The potential acoustic cues voice onset time (VOT), F0, and H1-H2 were measured and analyzed for 14,478 stops. Results indicated that in conversational speech (interview), SK speakers neutralized VOT between lenis and aspirated and used F0 robustly to differentiate the two categories, while distinguishing the long VOT for lenis and aspirated from the short VOT for fortis stops. In careful speech (reading one-syllable words), SK speakers differentiated all three categories by VOT. In contrast, NK speakers distinguished all three categories by VOT in all tasks, except for neutralizing the contrast for fortis and lenis in phrase reading. Furthermore, F0 was not used as robustly by NK as by SK speakers. We also examined the effects of age of arrival (AoA) and length of residence (LoR) on NK speakers' SDA. Our results indicated that the longer the NK refugees lived in SK, the more they could produce more SK-like stops. The results suggest that NK stop contrasts are likely distinguished by VOT, and these refugee speakers are in the process of acquiring SK stop patterns.